A relação entre tabagismo e habilidades sociais: uma revisão da literatura - Rondina, Regina de Cássia [UNESP] (My University, 2010)
The literature suggests an association between drug use and addiction and the repertoire of social skills of the individual. However, there are still relatively few studies focusing specifically on the relationship between smoking and social skills. Moreover, Brazilian studies on the subject are scarce. This paper presents a review of the literature about smoking and social skills, emphasizing the theoretical underpinning research, as well as the main data obtained so far. One of the most investigated issues is the relationship between assertiveness and smoking. It is assumed that the lack of assertiveness and in particular the ability to refuse the supply of drugs and / or peer pressure to consumption can be a risk factor for smoking initiation, especially in adolescents. However, the literature on this issue is still controversial. It is assumed that further studies to elucidate these associations could contribute to prevention programs and intervention for tobacco use, using social skills training as a strategy.

A literatura sugere associação entre consumo e dependência de drogas e o repertório de habilidades sociais do indivíduo. Contudo, ainda há relativamente poucos trabalhos enfocando, especificamente, a relação entre tabagismo e habilidades sociais. Além disso, ainda há escassez de estudos brasileiros sobre o assunto. Este trabalho apresenta uma revisão da literatura sobre tabagismo e habilidades sociais, destacando os alicerces teóricos que fundamentam as pesquisas, bem como os principais dados obtidos até o momento. Um dos temas mais investigados é a relação entre assertividade e tabagismo. Supõe-se que a falta de assertividade e, em especial, a habilidade de recusa à oferta de drogas e / ou pressão dos pares para o consumo possa ser fator de risco para iniciação do tabagismo, principalmente em adolescentes. Contudo, a bibliografia nesse sentido ainda é controversa. Novos estudos no sentido de elucidar essas associações, poderiam contribuir com programas de prevenção e intervenção para consumo de tabaco, que utilizem o treino em habilidades sociais como estratégia.
Relationship between smoking behavior and social skills: a literature review
Keywords: bulimia; tabagismo; habilidades sociais; prevenção